If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(wx + -1v) = 8(x + v) Reorder the terms: 3(-1v + wx) = 8(x + v) (-1v * 3 + wx * 3) = 8(x + v) (-3v + 3wx) = 8(x + v) Reorder the terms: -3v + 3wx = 8(v + x) -3v + 3wx = (v * 8 + x * 8) -3v + 3wx = (8v + 8x) Solving -3v + 3wx = 8v + 8x Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-8v' to each side of the equation. -3v + -8v + 3wx = 8v + -8v + 8x Combine like terms: -3v + -8v = -11v -11v + 3wx = 8v + -8v + 8x Combine like terms: 8v + -8v = 0 -11v + 3wx = 0 + 8x -11v + 3wx = 8x Add '-3wx' to each side of the equation. -11v + 3wx + -3wx = -3wx + 8x Combine like terms: 3wx + -3wx = 0 -11v + 0 = -3wx + 8x -11v = -3wx + 8x Divide each side by '-11'. v = 0.2727272727wx + -0.7272727273x Simplifying v = 0.2727272727wx + -0.7272727273x
| 63=.5(h)(7) | | 6+25=x+95 | | 2.4(10a+15)=2(9a+3) | | 5=5h | | 602.9=.333333333333(3.14)(36)(h) | | 22=2(3.14)(r) | | 4050=(27000)(.05)T | | 6*3x=1296 | | 2b+12=5b-12 | | y=3/2x-10 | | 3(w+7)+2w=5w+26 | | -12X^2+36X-27= | | 3x-18=5(x-6) | | t/3-7=9 | | 0=15t-2t^2-25 | | 4x+0.25y+0.5z=20 | | 5X-8X+3=8X(-3X+5) | | 5t-2=6t+8 | | 8m-27=45 | | 8h-2=4h+8 | | 7a(4a-2)= | | ln(3x+1)=0 | | 18(15z+19)= | | 400=(r-20)8 | | 26.4=.5r(6) | | (3a*3a*3a*3a)*(5a*5a)= | | 5+3(5X-6)=5-4(2X+1) | | 6x+58=10x-14 | | Y=4uv-3v | | 3(2x+5)-4(x+3)= | | 9a-3-13a+2=-4-4a+3 | | 4+35x=28x+13 |